A Method for Creating Scanned Map Metadata for Geoportals, Library Catalogs, and Digital Repositories: Reworking Existing MARC Records of Paper Maps to Create New Records for their Scanned Counterparts. Issue 2 (2nd September 2018) - Kiser, Tim; Smeltekop, Nicole
Abstract : This paper describes our process for creating metadata for digitized (scanned) maps, using the Machine-Readable Cataloging (MARC) records of the scanned maps' original paper counterparts as a starting point. Initially prompted by the need for metadata suitable for a consortial geoportal, we created new MARC records by applying a variety of programmatic edits using the software MarcEdit, as well as various manual edits as needed. These MARC records, in addition to supplying discrete records for the scans to our local catalog and WorldCat, served as the starting point for conversions to other metadata formats suitable for use in multiple discovery platforms, including the geoportal, our local digital repository, and the Digital Public Library of America (DPLA). The paper is therefore focused primarily on the MARC-to-MARC conversions – from descriptions of paper maps to descriptions of their scanned counterparts – that represent the first step of the conversions that followed.